Kinetics research of rice flour paste drying with beet colorant combined with energy supply - Dubkovetskyy, Igor; Malezhik, Ivan; Pasichnyi, Vasyl; Tymoshenko (Kremeshna), Irina (My University, 2014)
The aim of our research was to develop a method of stabilizing the natural pigment of betanine contained in beetroot juice, with its further use as a natural colorant in meat-containing products production. At the same time, to develop a comprehensive mix in dry form containing natural beet colorant with combination of rice flour, used as a cobuilder for mincemeat sausages.
Keywords: кафедра технології м’яса і м’ясних продуктів; кафедра процесів і апаратів харчових виробництв; combined method of exposure; paste; mushrooms; energy consumption; infrared drying; комбінований метод впливу; паста; гриби; споживання енергії; інфрачервона сушка